Дополнения к фауне комаров-лимониид (Diptera, Limoniidae) Северного Тянь-Шаня - Савченко, Е.Н. (Вестник зоологии, 1978)
A list of 17 species discovered on the Zailijsky Alatau mountain ridge for the first time is given in the article. The following species are new for the Soviet Union fauna: Dicranota (Rhaphidolapis) tumidosa Al., llisia (Parilisia)? fausta Al., I. (P.) multiserrata AL, Rhabdomastrix (Sacandaga) sp. and Antocha (5. str.) scapularis AL, new for the science — Dicranota (s. str.) bicornigera Sav., Dactylolabis (s. str.) opaca Sav., Ilisia (Parilisia) forcipula Sav. and I. (P.) latiloba Sav. All the new species are described and the male hypopygium are figured. The type specimens are preserved in the collection of the Institute of Zoology, Kiev.